Removal of Contaminants from Industrial Lean Amine Solvent Using Polyacrylamide Hydrogels Optimized by Response Surface Methodology - Priyabrata Pal; Fawzi Banat (Adsorption Science & Technology)
Response surface methodology (RSM) based on a three-level, three-variable model was used to optimize the preparation parameters of a hydrogel consisting of acrylamide (AAM) as monomer, N,N'-methylenebisacrylamide as cross-linker and ammonium peroxodisulphate as initiator. Considering percentage removal of total metal ions (contaminants) as the treatment response, the effects of three variables, namely, wt% AAM, wt% cross-linker and temperature of polymerization were investigated. The polyacrylamide (PAAM) hydrogel was obtained as small beads and optimized using RSM. The hydrogel was used for the removal of total metal ions and total organic acid anions (known as heat-stable salts , HSSs) from industrial lean methyl diethanolamine solvents (MDEA, 50 wt% used by Gasco, Habshan, Abu Dhabi for natural gas sweetening). The presence of heavy-metal ions and HSS is responsible for many problems such as corrosion, foaming and fouling of the equipment. The PAAM hydrogel was characterized by determining its cross-link density and diffusivity. Scanning electron microscopy and Fourier transform infrared spectroscopy analysis of the polymeric hydrogel explained the adsorption process. using the best-prepared hydrogel, the percentage removal of total metal ions and total organic acid anions was 74% and 24.26%, respectively. According to the Langmuir model, the maximum adsorption capacity of the hydrogel for total metal ions was 1.876 µ equivalence/g and 7.686 mg/g for organic acid anions. The adsorption kinetics obeyed pseudo-first-order model for metal-ions removal and the highest rate of chromium ion adsorption was observed at pH 10.33. The desorption studies showed that the percentage removal was consistent across five cycles of adsorption and desorption.